Offer Heterogeneity in a Two State Model of Sequential Search - Khandker, Rezaul (The Review of Economics and Statistics, 1988)
The econometric method in the C. Flinn and J. Heckman (1982) study for estimating a Markovian model of search unem ployment and job tenure is further augmented by introducing a possibi lity that jobs may differ by separation rates or nonwage attributes. A set of reservation wages is obtained as a solution to the value fun ctions. Differences in reservation wages estimate the compensating no nwage utility differentials among jobs. The unemployment spell distri bution is characterized as one of competing risk based on which type of job is finally accepted. The model is implemented using data from the Employment Opportunities Pilot Project. Copyright 1988 by MIT Press.